1995
DOI: 10.1017/s0266462300006863
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Rehabilitation Technologies in Stroke: Outcomes and Costs

Abstract: Initial functional ability (Barthel Index, mean 57) was found to be an important predictor of functional ability 1 year after stroke (mean 80) and for costs during the period. On average the total cost for a stroke patient was about SEK 200,000; the main expense, accommodation, averaged about SEK 140,000, while assistive devices amounted to SEK 2,600. Those who use assistive devices, although having achieved a high functional ability, perceive and rate their life situation (Nottingham Health Profile) considera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
1

Year Published

1995
1995
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 19 publications
(10 reference statements)
3
16
1
Order By: Relevance
“…A possibly better stroke unit effect for patients with severe stroke corresponds with the findings of other studies, which have shown that the severity of stroke influences the length of hospital stay 6,21 and the pattern of total utilization of both hospital and nonhospital care. 7,17 Furthermore, Stroke Unit Trialists' Collaborations' meta-analytic data indicate a more marked effect of stroke unit care for patients with severe stroke versus mild stroke. 44 In conclusion, the present study showed that the total costs the first year did not differ significantly between the treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…A possibly better stroke unit effect for patients with severe stroke corresponds with the findings of other studies, which have shown that the severity of stroke influences the length of hospital stay 6,21 and the pattern of total utilization of both hospital and nonhospital care. 7,17 Furthermore, Stroke Unit Trialists' Collaborations' meta-analytic data indicate a more marked effect of stroke unit care for patients with severe stroke versus mild stroke. 44 In conclusion, the present study showed that the total costs the first year did not differ significantly between the treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…Assistive technologies are used frequently by stroke patients (about So%, see e.g., (4)) in order to reduce or compensate for the lost functions. Patients who use assistive devices one year after suffering stroke perceive and rate their life situation as being considerably more impaired compared with those without assistive devices, even when adjustments for differences in functional ability are made (5). Lawrence & Christie (6) also showed that patients' lives are mainly influenced by their own response to their disabilities and not by the physical disabilities in themselves.…”
Section: Introductionmentioning
confidence: 99%
“…The resources spent on assistive devices during the first year after stroke are about 1% of the total cost of the rehabilitation programme (5,4). There are few studies on costs for assistive devices, but the additional costs incurred in the selection process have been estimated as being as high as the cost of the devices themselves (7).…”
Section: Introductionmentioning
confidence: 99%
“…The higher prevalence of hypertension found in the elderly [6] explains this observation, given the higher risk of CV complications, including heart failure, in the older population compared with younger hypertensives. Antihypertensive treatment [46,61,66] has been shown to reduce this risk in the elderly. The observation that 70% of the excess costs could be attributed to the minority of patients with BP >160/95 mmHg is not surprising, as the frequency of CHF and stroke increases greatly as BP exceeds 160/95 mmHg [13].…”
Section: Discussionmentioning
confidence: 99%
“…Costs were primarily obtained from government sources and published studies. Where published data was not available, costs were estimated using the product of OECD average length of stay (ALOS) data for the speci c CV event and the local per diem costs [18,[51][52][53][54][55][56][57][58][59][60][61][62][63][64][65]. …”
Section: Risk Of CV Eventsmentioning
confidence: 99%